Direct Selling dalam Usaha Perasuransian di Indonesia Perspektif Hukum Islam - Seri Utami Ningsih (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2020)
Insurance companies such as PT. Life Insurance Central Asia Raya, PT. Prudential Life Insurance, PT. Generali Indonesia Life Insurance, PT. Tugu Mandiri Life Insurance, PT. MNC Life Insurance, PT. Asuransi Jiwasraya (Persero), and PT. Sequis Life Life Insurance have marketed one of their insurance products with a direct sales system, or better known as direct selling, which was developed by insurance agents by recruiting insurance agents in a row. This paper explains how the Financial Services Authority (OJK) controls the marketing of insurance businesses and the view of Islamic law on the practice of direct selling in insurance marketing. Based on the type, this research is library research. The results showed that the Supervision of the Financial Services Authority was careless from the principles of legal certainty, professionalism, and openness. This is because Direct Selling was not included in the marketing channels stipulated in the Financial Services Authority Regulation (POJK) Number 23 of 2015 concerning Insurance Products and Marketing of Insurance Products. Based on the POJK, direct selling practiced by insurance companies is illegal. The Financial Services Authority emphasizes direct selling as the development of insurance marketing methods by the insurance agent. In the perspective of Islamic law, based on Sadd al-Dzari`ah, although basically direct selling is permitted, but the actions of the insurance agent have great potential to endanger the health of the insurance, and the negligence of the supervision of the Financial Services Authority, the law of this direct selling is haram (forbidden). Therefore, the Financial Services Authority must review the direct selling marketing developed by the insurance agent.